Combined effect of UV-C and ozone on bioactive compounds and microbiological quality of fresh-cut rocket leaves - Gutierrez, Diego Ricardo (2019)
The separate application of UV-C (25 kJ/m2, 380 s) and O3 gaseous (2.5 mg/L for 10 min) treatments and of their combination (25 kJ/m2 UV-C with 2.5 mg/L O3) were studied to evaluate the effect of combined treatments of UV-C and O3 on microbial counts, bioactive profile and sensory changes of fresh-cut rocket leaves throughout shelf life to determine whether these treatment have additive or synergistic. The separate application of UV-C and O3 and of their combination UV-C + O3 did not affect the sensorial quality, total chlorophyll contents, phenolic compound nor antioxidant capacity of fresh-cut rocket leaves. However, these treatments controlled better the growth of epiphytic microbes than untreated samples. The UV-C treatment had better effect at reducing microorganisms present and not significant differences were found as to the combined treatment. Therefore, applying the combined treatment UV-C + O3 had neither synergistic nor additive effect in the extension of the fresh-cut rocket leaves shelf life.